2012
DOI: 10.2169/internalmedicine.51.7626
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Pneumonia in the Community

Abstract: A 62-year-old man presented with general fatigue. He was diagnosed with septic shock and severe pneumonia. The sputum at admission yielded methicillin-sensitive Staphylococcus aureus (MSSA) strain and methicillin-resistant S. aureus (MRSA) strain. Despite antibiotic treatment, he did not improve. A chest computed tomography (CT) revealed multilobar cavity lesions. Only MRSA strain was confirmed at that time. We diagnosed him with necrotizing pneumonia. Despite treatment with vancomycin, his pneumonia worsened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…25,26,27 However, they may also be implicated in severe infectious conditions, such as meningitis, pneumonia, bacteremia, and septic shock. 28,29,30 Molecular analysis was consistent with presence of the mec A gene , contained in a clonal type IV SCC mec . Molecular findings also confirmed an increased antimicrobial susceptibility profile; this is attributableto the smaller cassette, which, in most cases, does not harbor other resistance-determining factors, unlike classic hospital-acquired strains.…”
Section: Discussionmentioning
confidence: 54%
“…25,26,27 However, they may also be implicated in severe infectious conditions, such as meningitis, pneumonia, bacteremia, and septic shock. 28,29,30 Molecular analysis was consistent with presence of the mec A gene , contained in a clonal type IV SCC mec . Molecular findings also confirmed an increased antimicrobial susceptibility profile; this is attributableto the smaller cassette, which, in most cases, does not harbor other resistance-determining factors, unlike classic hospital-acquired strains.…”
Section: Discussionmentioning
confidence: 54%
“…Based on our search of Medline and Igaku Chuo Zasshi (a tool for searching Japanese biomedical publications), no case series or controlled studies were identified. We could identify 8 cases (3 male and 5 female); 4 case reports were written in English, and 4 were written in Japanese and had been cited by both Japanese and English studies (age range: 16–77 years; median age: 44 years) (Table 1) [11], [12], [13], [14], [15], [16], [17], [18]. Among these cases, skin and soft tissue infections and necrotizing pneumonia were the main portal of entry.…”
Section: Discussionmentioning
confidence: 99%